PENGARUH METODE PEMBELAJARAN DAN KOORDINASI TERHADAP HASIL BELAJAR BOLAVOLI SISWA SMP 2 MAYONG JEPARA TAHUN 2011/2012 (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2012)
AbstractThe research was intended to find out the different effects of (1) cooperative and conventionalinstructional methods, (2) high and low eye-hand coordination and (3) interactions betweenthe two methods and eye-hand coordination on the outcomes of volley ball learning. Thisresearch used an experimental method and a 2 x 2 factorial design. The population for thisresearch consisted of 188 seventh-grade students (divided into 5 classrooms) of SMP N 2Mayong, Jepara, for Academic Year 2011-2012. The sample for this research was 152 studentsfrom 4 classrooms, taken using the technique of simple random sampling. By conducting eyehandcoordination test, 40 students were selected from the total sample. This sub sample wasdivided further into two categories of coordination groups: 20 high eye-hand coordination studentsand another 20 students of low eye-hand coordination group. The independent variablesconsisted of manipulative and attributive variables. The manipulative variables consisted ofcooperative and conventional instructional methods. The attributive variables consisted ofhigh eye-hand coordination and low eye-hand coordination. The dependent variables consistedof the learning outcomes of the students in volley ball playing. The data were collectedby means of preliminary tests and measurements on the student performances. The data onthe learning outcomes were collected by testing the accuracies of high, low and underhandservices. The data on the eye-hand coordination were collected by throws and catch (throwingand catching the ball). The data were then processed using variant analyses. The hypotheseswere tested using F-Tests, at a significance level of 5 % and t-test. The analyses produced thefollowing results. There were different effects of cooperative and conventional instructionalmethods and high and low eye-hand coordination on the outcomes of learning volley ball. Thecooperative method for the students in the high eye-hand coordination group produced bettereffects compared to the use of this method in the same group. Using the conventional methodfor the students in the high eye-hand coordination group also produced better effects comparedto the use of this method in the low eye-hand coordination group. The cooperative methodproduced better effects, than the conventional one, on the high eye-hand coordination group.However, when the cooperative method was used for the low eye-hand coordination group, itdid not produce better effects as compared to effects produced by the conventional method. Inconclusion, high eye-hand coordination was much better than low eye-hand coordination.